Biogeography and phylogenetic relationships of Hyrcanian wild apple using cpDNA and ITS noncoding sequences. Issue 3 (3rd April 2019) - Yousefzadeh, Hamed; Khodadost, Ali; Abdollahi, Hamid; Ali, Syed Shujait; Kozlowski, Gregor; Bina, Hamid
Abstract : The Hyrcanian forest of northern Iran is considered one of the potential centres for the evolution and domestication of the genus Malus (Rosaceae). However, the biogeography, phylogenetic position, and taxonomic status of the Hyrcanian wild apples have never been evaluated. In our study, the nucleotide sequences of the internal transcribed spacer (ITS) and the trn H -psb A intergenic spacer region from 14 natural populations were analysed. Phylogenetic analysis based on the ITS and the Maximum-likelihood (ML) tree showed that all Hyrcanian samples were closely related to M. orientalis and M. asiatica and can be placed within section Malus and series Malus . Furthermore, based on a comparison of ITS2 secondary structures, the Hyrcanian samples were identical to M. orientalis and M. sieversii . Biogeographic scenarios constructed using Statistical Dispersal-Vicariance Analysis (S-DIVA) and the Bayesian Binary Method (BBM) indicated that the ancestor of Malus originated during the Eocene, ∼53 million years ago (Ma), and that China played a vital role in the expansion of the range of the genus. The members of Malus colonized the Hyrcanian region from China during the Miocene, ∼22-10 Ma.